Symbolism in The Movie “Divergent”: Peirce’s Semiotic Analysis of The Faction’s Symbols - Nabila Balqis; Laili Etika Rahmawati (International Journal of Science and Environment (IJSE), 2026)
This study examines the symbolism of faction symbols in the movie Divergent through the semiotic perspective of Charles Sanders Peirce. The research focuses on how the symbols representing the five factionsAbnegation, Dauntless, Erudite, Amity, and Candorserve as visual signs that convey social identity and ideological values within the dystopian society portrayed in the film. This study applies a qualitative descriptive method using Peirces semiotic framework, which explores the relationship between representamen, object, and interpretant, as well as the classification of signs into icons, indexes, and symbols. The findings indicate that each faction symbol reflects distinct moral values: Abnegation symbolizes humility and self-sacrifice, Dauntless represents bravery and resilience, Erudite signifies intelligence and rational thinking, Amity embodies peace and harmony, and Candor reflects honesty and justice. The analysis further demonstrates that these symbols mainly function as symbolic signs, although some also contain iconic and indexical characteristics. In addition to serving as visual identifiers, the faction symbols operate as ideological instruments that strengthen social divisions, shape collective identity, and support mechanisms of social control within the dystopian social system. Overall, this study highlights that symbolism in Divergent plays a significant role in constructing meaning, identity, and ideology, while illustrating how visual symbols in film function as a medium for communicating social and ideological messages to audiences. Keywords: Charles Sanders Peirce, Divergent, Faction Symbols, Film Studies, Semiotic Analysis, Symbolism .